Study on the Development of Quality Measurements Models for Steering Business Services in Relation to Customer Satisfaction - Katrin Marquardt; Marieta Olaru; Ioana Ceausu (Amfiteatru Economic Journal, 2017)
The growing competition in the market, higher customer demands and globalisation forces the business service providers to improve their services much faster. Nowadays, it is not enough to provide good quality it is more important to delight the customers and to deliver more than they expect. Likewise, renowned research companies predicted that customer satisfaction will become the competitive differentiator within the next years. Thus, the main reasons of the present study are at first, establishing a common understanding on the term “quality” and presenting the relationship between customer satisfaction and service quality. Secondly, the study summarizes the identified factors, which mostly influence the customer satisfaction, as well as the common methods used to measure service quality in relation to these factors. Thirdly, the authors introduce and explain the newly developed six step model for establishing an effective measurement method for service quality and the proposed three level service quality model with the related measurements and outcomes. Both models will assist business service providers to protect and improve their service quality and with that their customer satisfaction. The methodology used for this research is a systematic literature review focused on subjects of quality, customer satisfaction and best-practice metrics for service quality. In addition, surveys and studies from well-known research companies were evaluated. The outcome of the study is always focused on the business service area.
Keywords: M55; L84; L86; L14; O14; 330; service quality; customer satisfaction; business services; service quality measurement models; performance indicators